I. INTRODUCTION: THE CO‐CONSTRUCTION OF MOTHER–CHILD ATTACHMENT RELATIONSHIPS IN EARLY CHILDHOOD. Issue 4 (5th December 2018) - Posada, Germán E.; Waters, Harriet S.
ABSTRACT: Attachment relationships are formed, organized, and elaborated through interactions between an attachment figure and her/his child. The parent–child codetermination process that establishes their relationship in infancy extends and expands during the preschool years. A child's developing ability to use her/his mother as a secure base requires support, time, and practice during early childhood. Moreover, experiences with attachment figures provide information that children use to build internal representations of their relationship. Thus, the organization of attachment behavior is expected to be related to the structure of a child's attachment representations. Yet, questions about how the structure of those representations develop remain unanswered. In moving into the preschool years, we anticipate that building of mental representations of secure base support and use will be guided by parent–child co‐construction processes. The child's improving language and advancing information processing skills increase the opportunities for verbally based interactions between caregiver and child. The mother–child co‐construction process of secure base relationships includes now a verbal‐representational component, but the nonverbal, behavioral building blocks remain in play as well.